The Relationship between the Availability of Family Toilets and Handwashing Behavior with the Incidence of Stunting in the Maratua Islands District, Berau Regency - Virda Putri Kumalasari; Rusdi Rusdi; Ainur Rachman (CV. AFDIFAL MAJU BERKAH, 2026)
Stunting remains a crucial public health problem in island regions such as the Maratua Islands District, Berau Regency, where poor sanitation and hygiene exacerbate chronic malnutrition in children under five. This study aimed to analyze the relationship between the availability of family latrines, handwashing behavior, and stunting incidence. Using a quantitative, observational, analytic cross-sectional design, a total sample of 54 children under five in the region was sampled. Instruments included a validated handwashing behavior questionnaire, a standardized latrine observation sheet, and WHO anthropometric measurements; data analysis included univariate frequencies, and Spearman correlation (α=0.05). The results showed a 100% prevalence of stunting (75.9% stunted, 24.1% severely stunted), with a significant correlation for handwashing behavior (ρ=0.350, p=0.009) but not significant for family latrines (ρ=0.227, p=0.098). Handwashing behavior is a top intervention priority over infrastructure in remote areas.